Synthesis Some of New Heterocyclic derivatives containing Azo Group - khdur, Radhiya.A. (Al-Qadisiyah Journal of Pure Science, 2017)
This paper is involved synthesis of Chalcone compound as starting material which used in synthesis of new heterocyclic derivatives from prepared compound previosly (D) [5-((acetyl phenyl)diazenyl)-2-hydroxy benzaldehyde] to give cyclic compounds such as Thiazine , Oxazine and 1,3- Oxazepine derivatives. These compounds have been characterized by T.LC , (FT-IR , H-NMR) Spectra , Elemental Analysis(C.H.N)and melting points.